Reading English Text on Screen vs Reading English Text on Printed-Book: A Phenomenological Study - Marpaung, Marlin Steffi (11th International Scholars Conference, 2019)
There are many people use their smartphones, tablets and computers to read English text. The use of gadget was popular to students to help them to improve their English skills especially reading. This study sought the preference of the students on reading which is reading on papers or reading on screen. The respondent of this study was 1% from total students enrolled for the short-semester, academic year 2018/2019. Each respondent was the representative from 5 majors; 1 from Accounting, 1 from Management, 1 from System Information, 1 from Mathematic Education, and 1 from Information Technology. The respondent was chosen randomly using the ballot system. The semi-structured interviews were utilized with open- ended questions. The semi-structured interview consisted of 10 questions and some followed- up questions to simplify and to make it easy for the students to understand the questions. The interviews were recorded, transcribed, and analysed in order to find out the answer of the research questions. The result of the study showed that the students prefer reading on screen instead of paper because it is easy to access and easy to carry everywhere. Three of the respondents was chosen handphone as the easier tool to use when reading English text. Based on the result, it is recommended for the English teachers to mix the teaching and learning process with new technique especially something that work with screen.